Construct validity of a student mathematics learning style instrument using exploratory factor analysis - Ahmad, Ahmad; Dos Santos, Mariano; Heniati Santosa, Farah; Ratu Perwira Negara, Habib (Journal of Didactic Mathematics, 2025)
This study seeks to validate the construction of mathematics learning style instruments for junior high school students using the Exploratory Factor Analysis (EFA) method. A total of 127 students from four schools in Central Lombok Regency, Indonesia, participated in this quantitative survey research. The instrument comprises 20 Likert scale statements designed to measure the various dimensions of a student’s mathematics learning style. The feasibility test of the data revealed a Kaiser-Meyer-Olkin (KMO) value of 0.75, and the results of Bartlett’s Test of Sphericity were significant (p < 0.001), indicating that the data was suitable for analysis using factor analysis. The results of the EFA employing the principal axis factoring and oblimin rotation methods yielded four primary factors: Visual Learning, Auditory Learning, Reading/Writing Style, and Kinesthetic Learning, which aligned with the VARK model. All items exhibited a dominant loading value of ? 0.51, with no significant cross-loading, suggesting a clean and well-defined factor structure. The balanced distribution of variance after rotation, coupled with theoretical suitability, supports the validity of the instrument’s construction. These findings suggest that this instrument is appropriate for use in academic research and educational practice, enabling teachers to design differential learning strategies that cater to students’ learning preferences, thereby enhancing engagement and learning outcomes.